Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.3171/jns.2005.102.2.0167
|View full text |Cite
|
Sign up to set email alerts
|

Is medial temporal injury responsible for pediatric postconcussion syndrome? A prospective controlled study with single-photon emission computerized tomography

Abstract: There exists significant MTH in pediatric patients with PPCS, which would imply that medial temporal lobe damage (involving the hippocampus and related structures) may occur after minor head injury and could be responsible for the symptoms of PPCS observed in this group of patients. Brain SPECT scans may thus help in the early identification of children prone to develop PPCS, and serial SPECT scanning may serve as a platform for testing the efficacy of various neurobehavioral and pharmacological interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
1
18
2
Order By: Relevance
“…To the latter point, traumatic microvascular impairment is a growing area of interest (Galgano et al, ) with preclinical studies reporting a reduction in capillary number/diameter (Park, Bell, Siddiq, & Baker, ) and reduced cerebral blood flow (Barkhoudarian et al, ) following injury. However, in contrast to previous pmTBI studies in sub‐acute pmTBI, there was no evidence of either hypoperfusion (Agrawal et al, ; Maugans et al, ) or hyperperfusion (Barlow et al, ; Stephens et al, ) post‐injury, reducing the likelihood of a pure vascular trauma for explaining current BOLD response abnormalities. Importantly, we cannot rule out trauma‐related changes in cerebral vascular reactivity (Metting et al, ) or alterations in neurovascular control using collected data.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…To the latter point, traumatic microvascular impairment is a growing area of interest (Galgano et al, ) with preclinical studies reporting a reduction in capillary number/diameter (Park, Bell, Siddiq, & Baker, ) and reduced cerebral blood flow (Barkhoudarian et al, ) following injury. However, in contrast to previous pmTBI studies in sub‐acute pmTBI, there was no evidence of either hypoperfusion (Agrawal et al, ; Maugans et al, ) or hyperperfusion (Barlow et al, ; Stephens et al, ) post‐injury, reducing the likelihood of a pure vascular trauma for explaining current BOLD response abnormalities. Importantly, we cannot rule out trauma‐related changes in cerebral vascular reactivity (Metting et al, ) or alterations in neurovascular control using collected data.…”
Section: Discussioncontrasting
confidence: 79%
“…Independent measures of cerebral blood flow (CBF) can disambiguate resting perfusion from other BOLD deficits following trauma (Mayer, Kaushal, et al, ). Hypoperfusion in the medial–temporal regions has been observed within 72 hr of injury and again at 3 months following pmTBI (Agrawal, Gowda, Bal, Pant, & Mahapatra, ), with deficits also associated with prolonged PCS. Findings of decreased CBF were replicated in the acute phase of sports‐related concussion (Maugans, Farley, Altaye, Leach, & Cecil, ), persisting up to 2 months post‐injury.…”
Section: Introductionmentioning
confidence: 99%
“…Similar patterns of reduced CBF have been found in children with concussion and adults immediately following concussion, as well as in the months and years following injury in a variety of brain areas including frontal, temporal, limbic, and occipital regions . Several SPECT studies also noted a negative relationship between post‐concussion symptoms and decreased CBF in frontal and temporal regions, or found (i) more severe hypoperfusion for patients with loss of consciousness compared to those who suffered concussions without loss of consciousness, or (ii) more severe medial temporal hypoperfusion in concussed children with persistent post‐traumatic symptoms compared to concussed children without persistent post‐traumatic symptoms …”
Section: Introductionmentioning
confidence: 55%
“…10 Most importantly, children with mild TBI displaying medial temporal hypoperfusion were more likely to show persistent PCS than those without these abnormalities. 10,11 Diffusion tensor imaging of the corpus callosum revealed that adolescents with mild TBI displayed less white matter integrity than controls and that a measure of white matter diffusion was significantly correlated with PCS severity. 8 …”
mentioning
confidence: 99%